Efficacy of cacao bean husk (L.Theobroma Cacao) extract in the reduction of plaque among orthodontic patients - de Lara-Torres, Angelica V.
Effective removal of dental plaque is compromised significantly when fixed orthodontic appliances are worn. Mouth rinse is used as an adjunct to mechanical oral hygiene measure in order to facilitate the control of dental plaque accumulation.
The main objective of this study was to test the effect a mouth rinse made from Cacao Bean Husk (CBH) extract in inhibiting plaque formation. The subjects included forty-five (45) patients from the Orthodontics Department of the 1301st GHQ Dental Dispensary, GHQ and HSC, Armed Forces of the Philippines.
A double blind cross over study design was employed in testing the effects of the 3 mouth rinses consisting of CBH extracts (experimental group), 29 % concentration of a commercially available mouth rinse (positive control) and placebo (negative control). This experimental study was patterned to the 4-day plaque regrowth model where the subjects have been allowed to gargle with their assigned mouth rinse as their only means of oral hygiene practice. The Turesky-Gilmore Glickman modification of Quigley-Hein Plaque Index was used to measure plaque accumulation on the involved tooth surfaces.
The data suggested that the mouth rinse made of CBH extract (experimental) and commercially available mouth rinse (positive control) were capable of reducing plaque accumulation as revealed by their low index scores at 4 days post treatment. When compared with the placebo (negative control) group, both the experimental and positive control groups exhibited statistically significant differences in terms of decreasing the amount of plaque build-up.
In conclusion, the mouth rinse made from CBH extract is an effective agent for controlling/inhibiting plaque formation in patients with orthodontic appliances.
Keywords: Cacao bean husk extract